Functional lateralization of lexical stress representation: a systematic review of patient data - Häuser, Katja; Domahs, Frank (Frontiers in Psychology, 2014)
According to the functional lateralization hypothesis (FLH) the lateralization of speech prosody depends both on its function (linguistic = left, emotional = right) and on the size of the units it operates on (small = left, large = right). In consequence, according to the FLH, lexical stress should be processed by the left (language-dominant) hemisphere, given its linguistic function and small unit size. We performed an exhaustive search for case studies of patients with acquired dysprosody due to unilateral brain damage. In contrast to previous reviews we only regarded dysprosody at the lexical level (excluding phrasal stress). Moreover, we focused on the representational stage of lexical stress processing, excluding more peripheral perceptual or motor deficits. Applying these criteria, we included nine studies reporting on 11 patients. All of these patients showed representational deficits in word stress processing following a lesion in their language-dominant hemisphere. In 9 out of 11 patients, it was the left hemisphere which was affected. This is a much more consistent pattern as found in previous reviews, in which less rigorous inclusion criteria may have blurred the pattern of results. We conclude that the representation of lexical stress crucially relies on the functioning of the language-dominant (mostly left) hemisphere.